Desentralisasi Asimetris Dalam Mewujudkan Kesejahteraan Masyarakat Pada Daerah Otonomi Khusus Papua - Herdanareswari, Intan (Fakultas Hukum Universitas Surabaya, 2024)
Abstract This paper describes the understanding of decentralization that develops into asymmetrical decentralization in special regions that are given privileges by the state, in this case a special autonomous region which will then describe how decentralization in Indonesia towards the Papua special autonomous region related to the form and structure of local government. Asymmetric decentralization is unavoidable as a result of a country that has a special autonomous region because a region that cannot be equated with other regions, so special treatment is needed for local governments in developing the potential of the region. The results of this study show that decentralization is the transfer of authority from the central government to the regions, and asymmetric decentralization itself is the transfer of authority to regions that are special and different from other regions. One of the asymmetrical decentralization to the Papua region is in the form of a regional government system that is different from other regions, where Papua has governing bodies such as the Papuan People's Representative Council, Papuan People's Assembly, and Governor whose position is different from other government bodies.